Who Are the True Venture Capitalists in Germany? - Tereza Tykvová (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
In this paper, we analyze the investment and divestment patterns of different types of venture capitalists. Using a data set em- bracing all venture-backed IPOs that occurred on Germany's Neuer Markt we investigate whether the governance structures, objectives, abilities and track records of different types of venture capitalists have a decisive influence on their behavior. Our main finding is that signifi- cant differences among the different types of venture capitalists exist. The behavior of independent and corporate venture capitalists is more similar to that of US funds whereas bank-dependent and public ven- ture capitalists typically are bridge investors rather than true venture capitalists. Our findings may be interesting for policy makers, for companies that seek capital and for venture capitalists who look for syndication partners.
Keywords: D82; G24; G32; 330; Venture Capital; IPO; Heterogeneity; Risikokapital; Neuer Markt; Wertpapieremission; Anlageverhalten; Deutschland